Simulation of three-dimensional fatigue crack propagation using enriched finite elements - Ayhan, Ali O. (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
A three-dimensional methodology for simulation of fatigue crack propagation is presented. The method is leveraged by the use of enriched crack tip elements to compute the mixed-mode stress intensity factors. The crack growth model used and the crack propagation life calculation are also described. As examples, fatigue crack propagation of a mode-I surface crack and crack advancements of mixed-mode surface cracks are simulated. The predicted results showed excellent agreement with experimental data from the literature. Thus, it is concluded that the crack propagation method developed allows efficient and accurate simulation of three-dimensional fatigue crack propagation problems. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Crack growth; Three-dimensional crack; Stress intensity factor; Enriched elements; Life prediction; STRESS INTENSITY FACTORS; SURFACE CRACKS; GROWTH; BRITTLE; XFEM; Computer Science; Engineering